A numerical study to determine the effect of strengthening and weakening of the transversus abdominis muscle on lumbar spine loads. Issue 16 (9th December 2020) - Nowakowska-Lipiec, Katarzyna; Michnik, Robert; Linek, Paweł; Myśliwiec, Andrzej; Jochymczyk-Woźniak, Katarzyna; Gzik, Marek
Abstract: This work aimed to determine the influence of strengthening or weakening of the transversus abdominis (TrA) muscle on loads in the lumbar spine using musculoskeletal modelling methods. The input kinematic data of two positions (a standing position and a position during a sitting-down task) were angles in the elbow joint (0°;4°), shoulder joint (0°;3°), hip joint (0°;75°) and knee joint (0°;69°) as well as the torso tilt angle (0°;32°). It was shown that a change in the TrA physiological cross section area (PCSA) has a crucial impact on lumbar spine loads (2xTrA PCSA causes a reduction in the force in joint L5–S1 by 11% for a standing position and by 25% for a sitting-down position) and value of intra-abdominal pressure.